1965
DOI: 10.1111/j.1151-2916.1965.tb11784.x
|View full text |Cite
|
Sign up to set email alerts
|

Phases in the Binary Systems PbO—La2O3, Gd2O3, and Sm2O3

Abstract: I n the binary system PbO-Laz03 only one compound, 4 P b 0 .Laz03, exists ; it is flanked by two eutectics. The structure of the compound, although of lower symmetry, is intimately related to the C modification of the rare earths. Below 800' to lOOO"C, metastable solid solutions are formed from oxide mixtures coprecipitated from mixed solutions of the nitrates, the cubic parameter a = 5.66 A, if extrapolated to pure LazO3, corresponding to half the a parameter of t h e C form of Laa03. The solid solutions exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1974
1974
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…However, with further increase in additive content (Ն6 mol% La) sintering starts at a much higher temperature of 850°C. This behavior could be explained by the presence of the secondary phase La 2 O 3 ⅐4PbO, which is probably formed by solidstate reaction at temperatures below 600°C and melts at 850°C in accordance with the phase diagram of Warzee et al 22 The existence of a secondary phase could be observed by optical microscopy, but the volume fraction was too small for a chemical analysis by SEM/EDX. Densification of all samples was characterized by the final relative densities which were determined by image analysis and the Archimedes method.…”
Section: (1) Densification Behavior and Microstructural Developmentmentioning
confidence: 60%
“…However, with further increase in additive content (Ն6 mol% La) sintering starts at a much higher temperature of 850°C. This behavior could be explained by the presence of the secondary phase La 2 O 3 ⅐4PbO, which is probably formed by solidstate reaction at temperatures below 600°C and melts at 850°C in accordance with the phase diagram of Warzee et al 22 The existence of a secondary phase could be observed by optical microscopy, but the volume fraction was too small for a chemical analysis by SEM/EDX. Densification of all samples was characterized by the final relative densities which were determined by image analysis and the Archimedes method.…”
Section: (1) Densification Behavior and Microstructural Developmentmentioning
confidence: 60%
“…2 and 3. At sintering temperatures below ∼1200°C, when La 2 Zr 2 O 7 is present (in the sample from powder calcined at 1050°C), it can dissolve in free PbO 7–9 . This leads to a lower temperature for the formation of a liquid grain boundary phase, together with a larger volume of grain boundary phase.…”
Section: Resultsmentioning
confidence: 99%
“…The second criterion is also met. See Phase diagrams by Fushimi and Ikeda 6 and by Warzee et al ., 7 which show that the solubility of PbZrO 3 in PbO varies from 3 to 6 wt% when going from 1100° to 1300°C. The corresponding numbers for PbTiO 3 in PbO are 50–100 wt%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The annealing process has mainly been used for rapid annealing of thin films of ferroelectric PLZT compositions 3,6 . These compositions contain more Ti than the antiferroelectric PLZT, and therefore the melting point of the PbO‐rich grain boundary phase will be lower and the solubility of PLZT material in the PbO phase will be increased 7–9 . Thus, it will be easier for the creation of a PbO‐free “clean” PLZT grain boundary phase in the titanium‐rich PLZT compositions.…”
Section: Introductionmentioning
confidence: 99%